Via : les années 1980-1990... (Paris : Musée des Arts Décoratifs, 1990)
Abdelkader, Abdi ; Bauchet, François ; Berthier, Marc ; Brunelle, Eugène ; Desombre, thibault ; Dubuisson, Sylvain ; Dumas, Rena ; Fauconnet, François ; Germanaz, Christian ; Jourdan, Eric ; Nouvel, Jean ; etc.
Via : les années 1980-1990..., Musée des Arts Décoratifs, Paris, du 24 avril au 26 août 1990
boek